2022
DOI: 10.3389/fpubh.2022.907124
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Internet Use on Commercial Health Insurance of Chinese Residents

Abstract: As a necessary supplement to social medical insurance, commercial health insurance is an important part of the Healthy China strategy. This study, based on the Chinese General Social Survey (CGSS) data in 2017, uses the probit model to analyze and study the internal relationship between Internet use and commercial health insurance purchase of urban and rural residents. The research results show that the use of the Internet significantly promoted commercial health insurance purchases of residents, and the promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…Kattih and Mixon (2020) [ 18 ] built a random coefficient model and concluded that age and gender have an important impact on the demand for commercial health insurance. Xu et al (2022) [ 2 ] built the Probit model based on the data of the China General Social Survey (CGSS) in 2017. The research results show that age, education level and income significantly promoted residents’ demand for commercial health insurance, but gender and marital status had no significant impact on the demand for commercial health insurance.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Kattih and Mixon (2020) [ 18 ] built a random coefficient model and concluded that age and gender have an important impact on the demand for commercial health insurance. Xu et al (2022) [ 2 ] built the Probit model based on the data of the China General Social Survey (CGSS) in 2017. The research results show that age, education level and income significantly promoted residents’ demand for commercial health insurance, but gender and marital status had no significant impact on the demand for commercial health insurance.…”
Section: Relevant Literature Reviewmentioning
confidence: 99%
“…Since the commercial health insurance industry of China resumed operation in 1982, its business scale has become increasingly large and its development speed has advanced rapidly [ 2 , 3 , 4 ]. In terms of the number of companies, this increased from 1 in 1982 to 164 in 2020; in terms of premium scale, this increased from CNY 57.4 billion in 2009 to CNY 817.3 billion in 2020, and the annual compound growth rate reached 24.78%, higher than the life insurance premium income of 10.22% and accident insurance premium income of 14.55% in the same period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, CGSS is a national, comprehensive academic survey that collects data at multiple levels of society, community, family, and individuals. CGSS data are widely used in studies of health and Internet use ( 64 67 ). Considering the timeliness and availability of the data, we selected cross-sectional data from the latest released 2017 CGSS as the samples for this study.…”
Section: Data Sources and Specification Of Variablesmentioning
confidence: 99%
“…Family asset allocation behavior not only determines family living standards [ 3 , 4 ], but also has an important impact on national economic development. After the implementation of the reform and opening-up policy, the commercial health insurance industry switched into the fast development lane [ 5 ]. In terms of insurance density, the per capita density of commercial health insurance increased from CNY 50.52 in 2010 to CNY 578.82 in 2020.…”
Section: Introductionmentioning
confidence: 99%